2010
DOI: 10.1007/s11274-010-0393-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gallic acid and catechin polyphenols on probiotic properties of Streptococcus thermophilus CHCC 3534 strain

Abstract: The study aimed at assessing the potential influences of two polyphenolic compounds on growth and some recently proven probiotic attributes of Streptococcus thermophilus CHCC 3534. The strain was tolerant to 0.8% gallic acid and 0.3% catechin. Gallic acid and catechin adapted cells were moderately to highly sensitive to most antibiotics, and to low pH (2.0) compared to the parental cells. Gallic acid adapted cells survived pHs 3.0 and 4.0, and were rapid b-galactosidase producers. Catechin adapted cells demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
2
22
0
1
Order By: Relevance
“…Thus, hawk tea of 2% and 4% promoted the growth of S. thermophilus, L. acidophilus, and L. casei to varying degrees. Similar results were obtained by Khalil (2010) and Story, Azcarate-Peril, Klaenhammer, and Harris (2009).…”
Section: Numbers Of Lactic Acid Bacteriasupporting
confidence: 87%
“…Thus, hawk tea of 2% and 4% promoted the growth of S. thermophilus, L. acidophilus, and L. casei to varying degrees. Similar results were obtained by Khalil (2010) and Story, Azcarate-Peril, Klaenhammer, and Harris (2009).…”
Section: Numbers Of Lactic Acid Bacteriasupporting
confidence: 87%
“…Alberto et al . and Khalil found that gallic acid could stimulate the growth of Lactobacillus hilgardii 5w and Streptococcus thermophilus CHCC 3534.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of sterile longan juice and free cells led to a significant increase (P ≤ 0.05) in both lactobacilli, presumably owing to the presence of a carbon source and some bioactive components such as gallic and ellagic acids in the juice. 21 Alberto et al 33 and Khalil 34 found that gallic acid could stimulate the growth of Lactobacillus hilgardii 5w and Streptococcus thermophilus CHCC 3534. The encapsulated cells of both probiotics were able to survive throughout the small intestinal section, with a gradual reduction by roughly 6 log cycles from the initial state.…”
Section: Discussionmentioning
confidence: 99%
“…At 0‐week ripening, the mean microbial counts of the control and NPSCC were not significantly different, but at 6‐week ripening, the mean microbial counts (5.00 × 10 8 cfu/mL) of NPSCC were significantly higher than those (2.60 × 10 8 cfu/mL) of the control. According to Khalil (), polyphenols such as gallic acid and catechin can improve the growth of Streptococcus thermophilus . Therefore, in the present study, it is assumed that the nanopowdered peanut sprout could be used as an excellent nutritive source for lactic acid bacteria growth during cheese ripening.…”
Section: Resultsmentioning
confidence: 99%